The Correlation between Watching YouTube video and the Students’ Speaking Ability at English Education Department of University of Islam Malang - NURUL SYAFIKA (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: YouTube is one of the media to improve students' English speaking ability. Watching YouTube videos are an interesting medium that gives students better exposure to aspects of speaking skills. In this study, the researcher used quantitative approach. The participants of this research were 20 students of the fourth semester of English Department of University Islam Malang. The researcher chooses A class to be the participants of this study. In investigating this study, the researcher used questionnaire from Hikmah (2020) and speaking score from Speaking IV lecturer for collecting the data. The finding represented that there was a correlation between students’ watching YouTube video and speaking ability. The significance value calculated 0.040 is smaller than 0.05 (P-value = 0,040 < 0.05). This means, that the hypothesis (H0) was rejected and the null hypothesis (H1) was rejected. It can be concluded that there is significantly correlation between students’ watching YouTube video and speaking ability. In conclusion, 20 students from A class at the fourth semester are students who have good speaking scores which are influenced by watching English YouTube videos especially in speaking. By using YouTube videos as learning media, students can more easily improve their learning abilities, especially in speaking material. This shows that they understand the explanation given by the teacher and from watching YouTube videos. Keywords: Correlation, YouTube video, Speaking ability